Wonderstruck - Selznick, Brian (New York : Scholastic, 2011)
Having lost his mother and his hearing in a short time, twelve-year-old Ben leaves his Minnesota home in 1977 to seek the father he never knew in New York City, and meets there Rose, who is also longing for something missing from her life. Ben's story is told in words; Rose's in pictures.
Includes bibliographical references.
Keywords: American Museum of Natural History -- Fiction; American Museum of Natural History -- Fiction; Families -- Fiction; Diorama -- Fiction; Deaf -- Fiction; People with disabilities -- Fiction; Museums -- Fiction; Runaways -- Fiction; Family life -- Fiction; Diorama -- Fiction; Deaf -- Fiction; Physically handicapped -- Fiction; Museums -- Fiction; Runaway children -- Fiction; New York (N.Y.) -- History -- 20th century -- Fiction; New York (N.Y.) -- History -- 20th century -- Fiction